Region-Specific Effects of Immunotherapy With Antibodies Targeting α-synuclein in a Transgenic Model of Synucleinopathy - Kallab, Martin; Herrera-Vaquero, Marcos; Johannesson, Malin; Eriksson, Fredrik; Sigvardson, Jessica; Poewe, Werner; Wenning, Gregor K.; Nordström, Eva; Stefanova, Nadia (Frontiers in Neuroscience, 2018)
Synucleinopathies represent a group of neurodegenerative disorders which are characterized by intracellular accumulation of aggregated α-synuclein. α-synuclein misfolding and oligomer formation is considered a major pathogenic trigger in these disorders. Therefore, targeting α-synuclein species represents an important candidate therapeutic approach. Our aim was to analyse the biological effects of passive immunization targeting α-synuclein and to identify the possible underlying mechanisms in a transgenic mouse model of oligodendroglial α-synucleinopathy. We used PLP-α-synuclein mice overexpressing human α-synuclein in oligodendrocytes. The animals received either antibodies that recognize α-synuclein or vehicle. Passive immunization mitigated α-synuclein pathology and resulted in reduction of total α-synuclein in the hippocampus, reduction of intracellular accumulation of aggregated α-synuclein, particularly significant in the spinal cord. Lowering of the extracellular oligomeric α-synuclein was associated with reduction of the density of activated iba1-positive microglia profiles. However, a shift towards phagocytic microglia was seen after passive immunization of PLP-α-synuclein mice. Lowering of intracellular α-synuclein was mediated by autophagy degradation triggered after passive immunization in PLP-α-synuclein mice. In summary, the study provides evidence for the biological efficacy of immunotherapy in a transgenic mouse model of oligodendroglial synucleinopathy. The different availability of the therapeutic antibodies and the variable load of α-synuclein pathology in selected brain regions resulted in differential effects of the immunotherapy that allowed us to propose a model of the underlying mechanisms of antibody-aided α-synuclein clearance.